GRASSES INDIGENOUS TO ALASKA AND ICELAND COMPARED WITH INTRODUCED GRASSES FOR FORAGE QUALITY - MITCHELL, Wm. W. (Canadian Journal of Plant Science, 1987)
Entries of red fescue (Festuca rubra), bluejoint reedgrass (Calamagrostis canadensis), polargrass (Arctagrostis latifolia), Bering hairgrass (Deschampsia beringensis), and tufted hairgrass (D. caespitosa), native to Alaska or Iceland, were compared with entries of timothy (Phleum pratense), bromegrass (Bromus inermis), meadow foxtail (Alopecurus pratensis), and creeping foxtail (A. arundinaceus), of more southern origin, for forage quality characteristics in a trial at Palmer, Alaska. The grasses were sampled at head emergence and after 30–32 d regrowth in 1982; in 1983 initial growth was sampled weekly for 11 w commencing 13 May. The native grasses were generally as high and sometimes significantly higher in N and P percentages than the introduced grasses. Red fescue and Bering hairgrass tended to be the highest in N and red fescue and polargrass the highest in P concentrations. Bromegrass was notably low in P content. Timothy and bromegrass were often the highest in IVDMD, and bluejoint and tufted hairgrass tended to be the lowest. The average daily rate of decline in IVDMD for timothy and bromegrass over the 1983 sampling period approximated the 4.8–5 g kg −1 reported by others. However, rates of decline varied considerably from week to week and generally were highest during the first 4–6 wk. The native entries manifested sufficient potential in quality to merit further consideration for forage use.Key words: Alopercurus, Arctagrostis, Bromus, Calamagrostis, Deschampsia, Festuca, Phleum